2018
DOI: 10.3390/molecules23123319
|View full text |Cite
|
Sign up to set email alerts
|

Schisandra Chinensis Lignans Suppresses the Production of Inflammatory Mediators Regulated by NF-κB, AP-1, and IRF3 in Lipopolysaccharide-Stimulated RAW264.7 Cells

Abstract: Schisandra Fructus (SF) is a traditional Chinese herb used in the treatment of inflammatory disorders like hepatitis. One of the main anti-inflammatory components of SF is the lignans. However, the underlying anti-inflammatory mechanism of Schisandra Chinensis lignans (SCL) remains unclear. This study aims to investigate the effects of SCL on inflammatory mediators in lipopolysaccharide-stimulated RAW264.7 cells and explore the underlying mechanism. The production of nitric oxide (NO) was determined by Griess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…It has been reported that LPS activates the TLR4 signaling pathway and subsequently produces pro-inammatory cytokines and chemokines in the macrophage cells. 15,26,27 In line with the previous studies, we observed that LPS remarkably promoted the release of pro-inammatory cytokines (see Following LPS stimulation, NF-kB, AP-1, and IRF3 are activated by post-translational modications, and translocate into the nucleus to induce the transcription of the pro-inammatory cytokines and chemokines. 28,29 Therefore, we rstly investigated the nuclear translocation of these three transcription factors by Western blot analysis.…”
Section: Effect Of Ris On the Production Of Pro-inammatory Cytokinessupporting
confidence: 87%
See 2 more Smart Citations
“…It has been reported that LPS activates the TLR4 signaling pathway and subsequently produces pro-inammatory cytokines and chemokines in the macrophage cells. 15,26,27 In line with the previous studies, we observed that LPS remarkably promoted the release of pro-inammatory cytokines (see Following LPS stimulation, NF-kB, AP-1, and IRF3 are activated by post-translational modications, and translocate into the nucleus to induce the transcription of the pro-inammatory cytokines and chemokines. 28,29 Therefore, we rstly investigated the nuclear translocation of these three transcription factors by Western blot analysis.…”
Section: Effect Of Ris On the Production Of Pro-inammatory Cytokinessupporting
confidence: 87%
“…47 TBK1 can phosphorylate IRF3 and promotes it nuclear translocation, leading to the expression of IFN-b and CCL-5. 27 Our data represent that the nuclear and phosphorylation levels of IRF3 as well as the phosphorylated TBK1 were decreased by the RIS treatment, indicating that RIS impeded the LPS-induced TBK1/IRF3 axis.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Subsequently, the secretion of these cytokines and chemokines were increased, which was necessary to activate the inammatory response. 23 To examine the inhibitory effect of XQEO on the gene expression of pro-inammatory cytokines Effects of the XQEO on the LPS-induced overproduction of pro-inammatory cytokines and chemokines in the RAW264.7 macrophages…”
Section: Chemical Proling Of the Xqeo By Gc-msmentioning
confidence: 99%
“…The nuclear translocation of transcription factors, such as NF-kB, AP-1, and IRF3, is considered a prerequisite for the transcription of genes associated with inammatory processes. 23 Therefore, in the present study, we also explored the effect of XQEO on the nuclear translocation of these transcription factors in the RAW264.7 cells. As shown in Fig.…”
Section: Chemical Proling Of the Xqeo By Gc-msmentioning
confidence: 99%